Examining musical sophistication: A replication and theoretical commentary on the Goldsmiths Musical Sophistication Index. (December 2020) - Baker, David John; Ventura, Juan; Calamia, Matthew; Shanahan, Daniel; Elliott, Emily M.
The difficulties associated with measuring the complex construct of musicianship have received considerable attention in the music psychology literature. Multiple measures exist for various constructs, yet the need for the careful replication and documentation of the use of these measures remains an area of critical importance. Here, we describe the replication of the Goldsmiths Musical Sophistication Index (Gold-MSI) in a sample of 346 university students, drawn from both a school of music and a department of psychology. The original approach to modeling the Gold-MSI was followed as closely as possible, and the results replicated well overall. Issues were noted, however, with the characteristics of the sample, the skew of some of the individual items, and the overall use of the bifactor structure. These findings are discussed in relation to the state of measuring musicianship in the current literature, as well as in relation to the larger theoretical concerns surrounding the modeling of complex psychological and musical constructs.